Deviation in Poetry of Indian Style - محمد رضایی; آرزو نقی زاده (مطالعات زبانی و بلاغی)
Style generally means expression. According to the formalists, when the author is seeking literary text, he must have a standard language and literary norms that are beyond and alienation and defamiliarization do literary test. defamiliarization done is two ways: extra regularity and Deviation. For the first time, Jeffrey leaches divided deviation into eight parts. It contains lexical, phonetic, written, semantic, stylistic, grammatical and archaism deviation.  The share of each of the deviations is different in different periods of literature and in a manner different from literary texts. It included at the beginning of tenth centuries in Indian style, to evade existing norms of the lyrics timuri and with using the deviation created contributions in the field of language. This article tries to identification of deviation types and mention of examples of the lyrics of the period.